Carbohydrate Sensing Through the Transcription Factor ChREBP - Ortega-Prieto, Paula; Postic, Catherine (Frontiers in Genetics, 2019)
Carbohydrate response element binding protein (ChREBP) is a glucose-signaling transcription factor central for the regulation of glycolysis and de novo lipogenesis in the liver. In response to glucose, ChREBP (α) undergoes several post-translational modifications (PTMs) (dephosphorylation, acetylation and O-GlcNAcylation) that will either modulate its cellular location and/or its transcriptional activity. Mlx (max-like protein x), a member of the Myc/Max family of bHLH/LZ transcription factors, is an obligatory partner of ChREBP. Both factors bind as a heterotetramer on a DNA regulatory element found within the promoter regions of glucose sensitive genes called carbohydrate response element (ChoRE). A novel isoform of ChREBP, named ChREBPβ, was also described in liver and adipose tissue. This ChREBPβisoform is lacking the low glucose inhibitory domain (LID) in its N-terminal domain and is described as a highly active isoform. However, despite growing interest, little is known about ChREBPβ regulation and its specific transcriptional function. In this review, we recapitulate recent progress concerning the mechanisms regulating the activity of ChREBP isoforms, including PTMs, novel partners and cofactors and finally the metabolic pathways they regulate in target metabolic tissues.